COVID-19 in Sammelunterkünften für Geflüchtete: Analyse von Pandemiemaßnahmen und prioritäre Bedarfe aus behördlicher Sicht - Biddle, Louise; Jahn, Rosa; Perplies, Clara; Gold, Andreas W.; Rast, Eilin; Spura, Anke; Bozorgmehr, Kayvan (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2021)
Background. The containment of the COVID19 pandemic in collective accommodation centres is crucial to maintain the physical and mental health of refugees. It is unclear what measures have been taken by authorities in this setting to reduce the risk of infection, minimise stressors for refugees during the pandemic and communicate containment measures.
Gesehen am 24.04.2023